If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -14 = -74 Reorder the terms: -14 + 5x = -74 Solving -14 + 5x = -74 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 5x = -74 + 14 Combine like terms: -14 + 14 = 0 0 + 5x = -74 + 14 5x = -74 + 14 Combine like terms: -74 + 14 = -60 5x = -60 Divide each side by '5'. x = -12 Simplifying x = -12
| 4x+5=7x-22 | | (1x^2)=9 | | 7x+2=-3+3x+13 | | 27+x=3-3x | | -12x-15=9 | | 3v-9=4u | | -0.5x+1=0.5x-5 | | X+12=33 | | 8t=5t+12 | | S+12=3s | | -6a-15=-3(a-7) | | -11-(-7)= | | 6x-4y=-6 | | -x+3+6x-9=34 | | 5r+7=6r | | 123-5x=4x+24 | | 0.5x+1=0.5x-1 | | 5q+9=3(q-5)+7 | | -28+18= | | 2(p+7)=5(p-7) | | 28+(-18)= | | 8x-1-5x=14 | | -1=-x-4 | | -6(4-n)=12n | | 5x-1260=x | | 7x+15=100 | | M+9=6(m+11) | | 5x+5=0.2x+29 | | K+2(k-5)=2k+2 | | 3x+6+4x=27 | | -9j+7=3j+19 | | (-3x^2yz)= |